Contaminant Hydrogeology - Part 1: Physical Processes - Cherry, J.; Gilham, R.; Pickens, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary Water-supply hydrogeology and contaminant hydrogeology occupy very different parts of the scientific spectrum; the former is based on aquifer hydraulics, soil mechanics, macrostratigraphy. and interpretation of groundwater flow systems in terms of volumetric flow rates In contrast, the latter depends on microstratigraphy, pore water velocities, hydrodynamic dispersion, and hydrogeochemistry Most of the methodology developed for water-supply hydrogeology is not well suited for contaminant hydrogeology. The purpose of Part 1 of this article is twofold:- 1) to review the geologic and hydrodynamic controls of the movement of dissolved contaminants in shallow groundwater flow systems. and 2) to outline the nature of some of the tools available to the hydrogeologist investigating the physical aspects of goundwater contamination and to indicate some of the problems that may arise in their use. The geochemical aspects of contaminant hydrogeology will be discussed in Part 2 by Jackson and Cherry, m a future issue of Geoscience Canada.